Successful rescue of fulminant myocarditis with mechanical circulatory support and immunosuppression therapy: A case report - Zhou, Chi (Frontiers in Cardiovascular Medicine, 2023)
Myocarditis is challenging to diagnose because of its various clinical manifestations. Fulminant myocarditis (FM) is a severe type of myocarditis characterized by heart failure, malignant arrhythmia, cardiogenic shock, and cardiac arrest. Its early diagnosis and timely treatment are crucial for a positive long-term prognosis. Here we report a case of 42-year-old woman who presented with fever, chest pain, and cardiogenic shock. An initial examination showed increased myocardial enzyme levels and diffuse ST-segment elevation. Urgent coronary angiography excluded coronary artery stenosis. Echocardiography revealed decreased left ventricular systolic function. Cardiac magnetic resonance imaging revealed cardiomyocyte necrosis and interstitial inflammatory edema. The patient was diagnosed with FM and administered antiviral and anti-infective agents, glucocorticoid, immunoglobulin, and supported with temporary cardiac pacemaker and positive airway therapy, and treated with continuous renal replacement therapy. As her clinical condition deteriorated rapidly, we immediately started an intra-aortic balloon pump and veno-arterial extracorporeal membrane oxygenation. She was discharged on day 15 and recovered normally during follow-up. The early initiation of mechanical circulatory support and immunosuppression are life-saving tools for the treatment of FM.